2016
DOI: 10.17576/3l-2016-2203-06
|View full text |Cite
|
Sign up to set email alerts
|

Citation Practice in the Whole TESOL Master’s Theses by Vietnamese Postgraduates

Abstract: Citing previous works is an important rhetorical feature of academic writing and it is challenging for novice writers, especially non-native English writers (NNEWs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
3
0
3
Order By: Relevance
“…Hyland (1999) maintains that integral and non-integral citations as well as utilization of reporting verbs are major sources for attributing the work of others. Nguyen and Pramoolsook (2016) suggest that more emphasis should be placed on authorship claims through integral citations because they entail the specific reference/name of the author in comparison to non-integral citations. Appropriate exploitation of reporting verbs affects the citation practices; besides this, it also strengthens the worth of claims reported to persuade the audience.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyland (1999) maintains that integral and non-integral citations as well as utilization of reporting verbs are major sources for attributing the work of others. Nguyen and Pramoolsook (2016) suggest that more emphasis should be placed on authorship claims through integral citations because they entail the specific reference/name of the author in comparison to non-integral citations. Appropriate exploitation of reporting verbs affects the citation practices; besides this, it also strengthens the worth of claims reported to persuade the audience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings of the study revealed substantial differences regarding the utilization of reporting verbs between the corpora of native and non-native writers. Nguyen et al (2016) explored the verbs used for citations in of dissertations of M.A TESOL. The corpus of the study contained 24 literature review sections from the research theses of Vietnamese students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…De mayor interés para nuestro estudio resulta la exploración de la variabilidad entre los géneros. El comportamiento de las citas se ha investigado principalmente en el artículo de investigación (entre otros, Swales, 1990;Hyland, 1999;Fløttum, Kinn y Dahl, 2006;Mur-Dueñas, 2009) y la tesis doctoral (entre otros, Dong, 1996;Thompson y Tribble, 2001;Gallardo, 2010;Soler-Monreal y Gil-Salom, 2011), aunque en los últimos años ha venido creciendo la atención prestada a la práctica de la citación en el género que analizamos en este artículo, el Trabajo de Fin de Máster (Petrić, 2007;Jalilifar, 2012;Rabab´ah y Al-Marshadi, 2013;Samraj, 2013;Sánchez-Jiménez, 2013, 2016, 2018a, 2021Oskueia y Kuhi, 2014;Nguyen y Pramoolsook, 2016), así como en los cursos universitarios de grado (Mansourizadeh y Ahmad, 2011;Luzon, 2015;Viemeyer, 2017;Wette, 2017;Lee, Hitchcock y Casal, 2018;Zhang, 2018;Gao, Picoral y Staples, 2021;Meihami y Esfandiari, 2021). En síntesis, se ha comprobado en estos trabajos que los escritores expertos utilizan una mayor variedad de funciones de las citas en sus textos dependiendo del propósito retórico de cada apartado del escrito, mientras que, por el contrario, los universitarios se limitan a reproducir el conocimiento sobre el tema investigado mediante la atribución del conocimiento a la fuente original en todo el texto, como informan de manera más específica los estudios que han contrastado la práctica de la citación entre la escritura académica de expertos y estudiantes universitarios (Mansourizadeh y Ahmad, 2011;Jalilifar, 2012;Sánchez-Jiménez, 2020a;Meihami y Esfandiari, 2021).…”
Section: Marco Teóricounclassified
“…Dentro de este marco teórico, nuestro trabajo viene a llenar un vacío epistemológico en la práctica de la citación dentro de la disciplina de la Lingüística Aplicada, terreno en el que tan solo se han producido tímidas incursiones en lo relativo al análisis de las citas en los textos redactados por estudiantes universitarios en el ámbito de la escritura académica (véase Sánchez-Jiménez, 2011), especialmente en lo que se refiere al contraste intercultural en el uso de las citas en el género académico del Trabajo de Fin de Máster (Jalilifar, 2012;Sánchez-Jiménez, 2013, 2016Rabab´ah y Al-Marshadi, 2013;Oskueia y Kuhi, 2014;Nguyen y Pramoolsook, 2016). De igual manera, a pesar de que las ramas de la Retórica Intercultural son extensas y se expanden por diversos campos del saber, son escasas las investigaciones realizadas sobre el objeto de estudio del presente artículo (véase Connor, 1996Connor, , 2011Panetta, 2000;Sánchez-Jiménez, 2020b).…”
Section: Introductionunclassified
“…Their findings suggested that teachers of EAP should make the teaching of these verbs explicit and let the learners have a more thorough understanding on how to deploy them. A study by Nguyen (2017) examined the use of reporting verbs in TESOL master dissertations written by Vietnamese students in a Vietnam university. Her findings showed that those Vietnamese TESOL MA students were not competent in using reporting verbs that critique other researchers' work.…”
Section: Reporting Verbs and Academic Writing Studiesmentioning
confidence: 99%